Regulatory Role and Potential Importance of GDF-8 in Ovarian Reproductive Activity - Zheng, Xiaoling; Zheng, Yongquan; Qin, Dongxu; Yao, Yao; Zhang, Xiao; Zhao, Yunchun; Zheng, Caihong (Frontiers in Endocrinology, 2022)
Growth differentiation factor-8 (GDF-8) is a member of the transforming growth factor-beta superfamily. Studies in vitro and in vivo have shown GDF-8 to be involved in the physiology and pathology of ovarian reproductive functions. In vitro experiments using a granulosa-cell model have demonstrated steroidogenesis, gonadotrophin responsiveness, glucose metabolism, cell proliferation as well as expression of lysyl oxidase and pentraxin 3 to be regulated by GDF-8 via the mothers against decapentaplegic homolog signaling pathway. Clinical data have shown that GDF-8 is expressed widely in the human ovary and to have high expression in serum of obese women with polycystic ovary syndrome. GDF-8 expression in serum changes dynamically in patients undergoing controlled ovarian hyperstimulation. GDF-8 expression in serum and follicular fluid is correlated with the ovarian response and pregnancy outcome during in vitro fertilization. Blocking the GDF-8 signaling pathway is a potential therapeutic for ovarian hyperstimulation syndrome and ovulation disorders in polycystic ovary syndrome. GDF-8 has a regulatory role and potential importance in ovarian reproductive activity, may be involved in folliculogenesis, ovulation, and early embryo implantation.